A5.7 Articular adipose tissue from OA patients is an important source of cytokines and adipokines. (31st January 2014) - Plebanczyk, M; Musialowicz, U; Burakowski, T; Janicka, I; Maslinski, W; Maldyk, P; Kontny, E
Abstract : Background and Objectives: Recently rheumatoid adipose tissue has been suggested to play an important role in chronic inflammatory joint diseases. Its ability to synthesize cytokines and adipokines has been characterised also in our Department. The aim of present work was to investigate whether adipose tissue obtained from Osteoarthritis (OA) patients also secretes factors relevant to disease pathogenesis and/or progression. Materials and Methods: Articular adipose tissue (AAT) and synovial membrane (SM) explants, obtained from OA patients who were undergoing knee joint replacement surgery, were cultured (100 mg/ml) for 24 hrs in medium (DMEM) alone or in the presence of LPS or cytokines: TNF, IFN-g, IL-1a, IL-15, IL-17 or IL-23. Concentrations of TNF, IL-1a, IL-6, IL-8, IL-1Ra, adiponectin and leptin were measured in culture supernatants by ELISA. Results: Untreated AAT spontaneously produced low levels of IL-6 and IL-8, while secretion of these cytokines by SM was significant. All stimuli increased IL-6 and IL-8 synthesis in AAT, but did not change it in SM. The levels of these cytokines were usually higher in SM than in AAT. Spontaneous secretion of TNF-a was negligible, LPS, IL-1a and IFN-g triggered marked TNF synthesis (in both tissues). Spontaneous production of IL-1a was also very low and rised only after LPS (AAT and SM) and TNF (SM) stimulation. SM stronger than AAT responded to stimulation. The level of anti-inflammatory IL-1Ra was high in both tissues (higher in SM than in AAT). Stimuli increased IL-1Ra production in AAT, but not in SM. The level of adiponectin was similar in tested tissues and stayed unaffected by stimulation. AAT and SM explants secreted spontaneously moderate amount of leptin. In AAT leptis secretion raised upon LPS and IL-1a stimulation, while stayed unchanged in SM. Conclusions: AAT, like SM, seems to be very active tissue. While spontaneous production of pro-inflammatory cytokines by AAT was low, it raised markedly upon stimulation. Moreover, AAT from OA patients produced spontaneously large amount of anti-inflammatory IL-1Ra. The secretion of classical adipokines did not differ between tissues. Therefore our results give direct evidence that in osteoarthritis, like in rheumatoid arthritis, adipose tissue is an active participant of cytokine and adipokines network.